The formation of isomeric pair in the natTi(3He,x)44m,gSc reactions: Effect of spin cut-off parameter on the isomeric ratio - Khandaker, Mayeen Uddin; Chakraborty, Animesh Kumer; Nagatsu, Kotaro; Obata, Honoka; Minegishi, Katsuyuki; Zhang, Ming-Rong; Okhunov, Abdurahim (Elsevier Ltd, 2021)
Excitation functions for the natTi(3He, x)44g,mSc nuclear reactions were measured from respective threshold up to 55 MeV by using a conventional stacked-foil activation technique combined with HPGe γ-ray spectroscopy. Individual cross-section values for the production of 44mSc and 44gSc were separated using a proper mathematical method on the basis of their individual gamma lines and the data for 44gSc are reported here for the first time. The default parameters of TALYS-1.8 are unable to provide the 44mSc/44gSc isomeric cross-section ratio values consistent with those obtained experimentally. However, an adjustment of the level density model and optical model potentials together with some other relevant parameters, especially the spin cut-off parameter with the variation of η (=Ieff/Irigid) were found to be effective to reproduce the measured cross-sections. A similar parameter adjustment could be useful for accurate prediction of other medium mass isomeric pairs (i.e., when the metastable state is longer-lived than the ground state) where either experimental data are not available, or an expensive experiment is required to obtain them.